Future of the Lome Convention : initial reflections on Europe's Africa policy after the year 2000 - Frisch, Dieter (European Centre for Development Policy Management MaastrichtNL, 1996)
Looks at the future of the Lome Convention after the year 2000 with special reference to Africa.